UPAYA KEDUTAAN BESAR REPUBLIK INDONESIA BUCHAREST DALAM MENINGKATKAN NATION BRANDING INDONESIA DI RUMANIA TAHUN 2018-2021 - Muzafarsyah Dwipayana (2023)
Cultural Diplomacy is an effort to exchange ideas, information, art and other cultural aspects between countries and their communities to build mutual understanding. Meanwhile, cultural diplomacy efforts were carried out by the Indonesian Embassy in Bucharest in 2018-2021 as an effort to increase Indonesia's Nation Branding in Romania. The background of the writer in making this thesis is based on the condition of Indonesian nation branding in Romania is still not optimal. Increasing nation branding is quite important because the reputation of a country may make it easier for that country to get important aspects in the form of interest and trust before carrying out bilateral cooperation with other countries which may fulfill the goals of the country's foreign policy. The research method is descriptive qualitative with data collection techniques in the form of interviews and assisted by literature review that based on books. The results of the research in this thesis show that cultural diplomacy to improve nation branding which was attempted by the Indonesian Embassy in Bucharest has been successful. Tourism numbers and other sectors have increased and the value of a positive national image has increased each period, but in 2020 there were yield constraints due to the Covid-19 pandemic. Based on the research results and conclusions, the researchers provide the following suggestions: The Indonesian Embassy in Bucharest should optimize digital technology more and work with well-known Romanian and Indonesian influencers to further expand the reach of forming Romanian public opinion on Indonesia. Keywords: Cultural Diplomacy, Indonesian Embassy Bucharest, Nation Branding, Indonesia, Romania